A.W. Greely papers - Greely, A. W. (Adolphus Washington), 1844-1935.; Greely, Henrietta Hudson Cruger Nesmith
Correspondence, letterbooks, memoranda, diaries, speeches, lectures, manuscripts and galley proofs of Greely's books and articles, notes, military papers, biographical material, Greely (Greeley) and Nesmith family papers, financial records, scrapbooks, clippings, printed matter, maps, memorabilia, and other papers relating primarily to his military career and exploration of the polar regions. Documents his service as a Civil War soldier; career in the U.S. Army Signal Corps; command of the U.S. Army's Dept. of the Columbia, Northern Division, and Pacific Division; leadership of the Lady Franklin Bay Expedition (1881-1884); direction of the construction of telegraph wire and cables worldwide; and supervision of relief work after the San Francisco earthquake and fire of 1906.
Subjects include the development of Alaska, polar regions, radio, United States Civil Service Commission, U.S. government role in science, Ute Indian journey of 1906, and reorganization of the U.S. Weather Bureau. Includes Greely's Civil War diary (1864); Henrietta Hudson Cruger Nesmith Greely papers; and a journal kept by a mate on the schooner United States on the Hayes Arctic Expedition (1860-1861).
Correspondents include Henry T. Allen, Roald Amundsen, Alexander Graham Bell, Henry Biederbick, Edward William Bok, David L. Brainard, William E. Chandler, Frank Moore Colby, Maurice Connell, Thomas A. Edison, Jesse Walter Fewkes, Frederick T. Frelinghuysen, Minnie L. Gardiner, William A. Glassford, Gilbert Hovey Grosvenor, William Babcock Hazen, S.P. Langley, Francis Long, Marchese Guglielmo Marconi, George W. Melville, William Mitchell, Robert E. Peary, Theodore Roosevelt, Charles Scribner, and William H. Taft.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
Explorer, U.S. Army officer, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allen, Henry T. -- 1859-1930 -- Correspondence; Amundsen, Roald, -- 1872-1928 -- Correspondence; Bell, Alexander Graham, -- 1847-1922 -- Correspondence; Biederbick, Henry, -- -1916 -- Correspondence; Bok, Edward William, -- 1863-1930 -- Correspondence; Brainard, David L. -- 1856-1946 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Colby, Frank Moore, -- 1865-1925 -- Correspondence; Connell, Maurice -- Correspondence; Edison, Thomas A. -- 1847-1931 -- Correspondence; Fewkes, Jesse Walter, -- 1850-1930 -- Correspondence; Frelinghuysen, Frederick T. -- 1817-1885 -- Correspondence; Gardiner, Minnie L. -- Correspondence; Glassford, William A. -- Correspondence; Grosvenor, Gilbert Hovey, -- 1875-1966 -- Correspondence; Hazen, William Babcock, -- 1830-1887 -- Correspondence; Langley, S. P. -- 1834-1906 -- Correspondence; Long, Francis, -- -1916 -- Correspondence; Marconi, Guglielmo, -- marchese, -- 1874-1937 -- Correspondence; Melville, George W. -- 1841-1912 -- Correspondence; Mitchell, William, -- 1879-1936 -- Correspondence; Peary, Robert E. -- 1856-1920 -- Correspondence; Scribner, Charles, -- 1854-1930 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Greeley family; United States. -- Army. -- Department of the Columbia; United States. -- Army. -- Northern Division; United States. -- Army. -- Pacific Division (1904-1911); United States. -- Army. -- Signal Corps; United States. -- Weather Bureau; United States Civil Service Commission; United States (Schooner); Disaster relief -- California -- San Francisco; Earthquakes -- California -- San Francisco; Fires -- California -- San Francisco; Radio; San Francisco Earthquake and Fire, Calif., 1906.; Science and state -- United States; Ship's papers -- 19th century; Telegraph; Ute Indians; Alaska -- History -- 1867-1959.; Arctic regions -- Discovery and exploration; Polar regions -- Discovery and exploration; United States -- History -- Civil War, 1861-1865.; Nesmith family; Army officers; Authors; Explorers